2020
DOI: 10.2196/23188
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Staff’s Experiences of Engagement When Introducing a Digital Decision Support System for Wound Management: Qualitative Study

Abstract: Background eHealth solutions such as digital decision support systems (DDSSs) have the potential to assist collaboration between health care staff to improve matters for specific patient groups. Patients with hard-to-heal ulcers have long healing times because of a lack of guidelines for structured diagnosis, treatment, and follow-up. Multidisciplinary collaboration in wound management teams is essential. A DDSS could offer a way of aiding improvement within wound management. The introduction of eH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…A shared understanding of the potential usefulness of the eHealth solution in wound management and engagement among others in the group, including stimulating and satisfactory leadership, were described as important for engagement over time. Collegial and organisational support being described as valuable in building positive experiences in implementation of eHealth solutions is supported by experiences from the introduction of the DDSS [ 17 ] and findings from a review conducted by Konttila and colleagues [ 27 ]. Kahn [ 28 ] also suggested that social connections, such as work interactions and interpersonal relationships, are crucial sources of meaning and that work climates characterised by openness and support help people dare to ‘risk’ being engaged.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A shared understanding of the potential usefulness of the eHealth solution in wound management and engagement among others in the group, including stimulating and satisfactory leadership, were described as important for engagement over time. Collegial and organisational support being described as valuable in building positive experiences in implementation of eHealth solutions is supported by experiences from the introduction of the DDSS [ 17 ] and findings from a review conducted by Konttila and colleagues [ 27 ]. Kahn [ 28 ] also suggested that social connections, such as work interactions and interpersonal relationships, are crucial sources of meaning and that work climates characterised by openness and support help people dare to ‘risk’ being engaged.…”
Section: Discussionmentioning
confidence: 99%
“…The DDSS is intended for use by multiple healthcare professionals, supporting them with structured processes for clinical teams to improve wound management: diagnosing and treating ulcers and reducing healing time and patient suffering. For more information, see previous publications [ 17 ]. Dermicus Wound is CE-certified as a Medical Device, Class I (D3.0–112,015), and compatible with iPhone devices, using a standard touchscreen user interface and camera.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations